Vaginal infections in pregnant women: diagnosis, new paradigms of therapy. A prospective study - Natalia M. Podzolkova; Tatiana P. Zefirova; Larisa G. Sozaeva; Dina A. Sadykova (Гинекология)
Background. Vaginal infection complicates the course of pregnancy and adversely affects perinatal outcomes for the mother and fetus. With the global increase in microorganism resistance to antimicrobial drugs, the treatment of vaginitis in pregnant women is not always effective, leading to recurrent pathology. Therefore, seeking new therapeutic solutions is a pressing task.